Patient-centered outcomes for clinical trials in chronic rhinosinusitis with or without nasal polyps and allergic fungal rhinosinusitis - Brittany Klooster; Kaitlin Chatterton; Nazifa Ibrahim; Madison C. Bernstein; Alan L. Shields; Veleka Allen (Journal of Patient-Reported Outcomes)
Abstract Background Chronic rhinosinusitis (inclusive of subtypes with nasal polyps [CRSwNP], without nasal polyps [CRSsNP], and allergic fungal rhinosinusitis [AFRS]) causes inflammation of the nose mucosa and paranasal sinuses. Unfortunately, evidence supporting use of clinical outcome assessments (COAs) in regulated clinical trials to assess key measurement concepts of these conditions is limited. Objective To identify key disease-related symptoms and impacts, potential outcomes of interest for new treatments, and COAs available to measure those outcomes among adult and adolescent individuals living with CRSwNP, CRSsNP, and AFRS. Methods Literature, clinical trial, and product label reviews were conducted to identify symptoms, impacts, and COAs used to assess CRSwNP, CRSsNP, and AFRS patient experiences in clinical trials. The disease related concepts identified in the literature were mapped to selected COAs to determine conceptual coverage of each COA. Results Twenty-five articles, twenty-five clinical trial records, and four product labels were included in the review. Across conditions, nasal obstruction, nasal discharge, and altered smell were the most frequently identified symptoms. The most frequently identified impacts of CRSwNP and CRSsNP were on emotional functioning and sleep, and adopting new behaviors for AFRS. Findings for key symptoms and impacts in adolescents were limited. More than 20 COAs used in these conditions were identified, and 14 COAs (e.g., Sinonasal Outcome Test [SNOT-22]) were evaluated for conceptual coverage of the concepts identified in the literature. Conclusion Results specify several symptom and impact outcomes, that if improved, would reflect treatment benefit for patients living with CRSwNP, CRSsNP, and/or AFRS. Several COAs demonstrated coverage of key measurement concepts and warrant further evaluation for use in clinical trials.